Prototype development of mecanum wheels mobile robot: A review - Abd Mutalib, Mohd Azri; Azlan, Norsinnira Zainul (Applied Research and Smart Technology (ARSTech), 2020)
This paper provides the review and prototype development of mecanum wheels mobile robot (MWMR). Nowadays, there is a high market demand for a wheeled machine or wheeled robot for various applications. The ability to move in any direction without altering even a single wheel makes this type of wheel useful for driving, especially in a narrowed or confined space. Various styles of implementing MWMR are discussed in this paper. The kinematic derivation and dynamic modelling are also presented. Characteristically, mecanum wheels face traditional mobile application issues like jerking and slippage, which contribute to low positioning accuracy and repeatability. Besides, environmental factors like disturbance and uncertainty also contribute to these issues. To eliminate or at least reduce the effect, the control strategies in previous researches have been reviewed and are presented in this paper. Finally, a low-cost prototype of MWMR was developed as an experimental platform for future study.